Application of Biophysical Techniques to Investigate the Interaction of Antimicrobial Peptides With Bacterial Cells - Gelmi, Maria Luisa; D'Andrea, Luca Domenico; Romanelli, Alessandra (Frontiers in Medical Technology, 2020)
Gaining new understanding on the mechanism of action of antimicrobial peptides is the basis for the design of new and more efficient antibiotics. To this aim, it is important to detect modifications occurring to both the peptide and the bacterial cell upon interaction; this will help to understand the peptide structural requirement, if any, at the base of the interaction as well as the pathways triggered by peptides ending in cell death. A limited number of papers have described the interaction of peptides with bacterial cells, although most of the studies published so far have been focused on model membrane-peptides interactions. Investigations carried out with bacterial cells highlighted the limitations connected to the use of oversimplified model membranes and, more importantly, helped to identify molecular targets of antimicrobial peptides and changes occurring to the bacterial membrane. In this review, details on the mechanism of action of antimicrobial peptides, as determined by the application of spectroscopic techniques, as well as scattering, microscopy, and calorimetry techniques, to complex systems such as peptide/bacteria mixtures are discussed.